Investigation of the performance of a slotted aerofoil at low Reynolds numbers - Obiga, Otuami (2018)
Slotted aerofoils have been suggested by numerous researchers as an effective means of controlling boundary layer flow separation, and improving aerodynamic performance. Numerous slot designs have been studied at high Reynolds number, but there is scarcity of study of such slots effect on aerofoil performance in low Reynolds number scenarios. In the present work, wind tunnel and numerical investigation of the effect of a unique slot configuration and its geometric parameters on the aerodynamic performance of a NACA0018 aerofoil at low Reynolds number was executed. The aim of this work is to ascertain if the unique slot configuration on the NACA0018 can improve the aerodynamic performance compared to a plain NACA0018, and if the slotted NACA0018 could be applied as rotors on a Darrieus-style vertical axis micro wind turbine for small scale energy conversion at low wind speeds. Four aerofoils were initially fabricated for the wind tunnel tests, each conforming to the NACA0018 profile; a plain aerofoil and three other slotted aerofoils, each with a span–length slot positioned at X=15%, X=45% and X=70% from the leading edge. The, chord length (c), span, slot slope (ψ) and slot width of the slotted aerofoils were 0.25m, 0.3m, 55° and 0.02c respectively. A 2D wind tunnel set up was used in testing the four aerofoils at Reynolds numbers of 92x103 138x103, 184x103 and 230x103, within 0° to 20° range of incidence. Comparing the slotted and plain aerofoils, the aerodynamic force data shows that the presence of the slots was detrimental to aerodynamic performance especially when the slot location is closer to the leading edge. Therefore, a 2D numerical parametric study of slot width and slope was carried out using ANSYS FLUENT 16.0 with the intention of improving the lift–to–drag (L/D) ratio of the span–length slotted aerofoils. Furthermore, a final slot configuration consisting of segmented slot pattern which incorporated the results of the parametric study was fabricated and tested in a wind tunnel. The aerodynamic force analysis shows a 50% increase in L/D ratio of the slotted aerofoil with slot position at X=70%, but its aerodynamic performance was still less than the Plain NACA0018. Thus this work proves that the suggested slot layout did not improve the aerodynamic performance of the NACA0018 aerofoil and as a result, it cannot be recommended to be used as a vertical axis wind turbine rotor. Finally, in order to improve the NACA0018 aerofoil performance, it was suggested that a new slot layout with slot slope on the pressure side inclined towards the leading edge should be designed and studied.